The English Course Materials Needs for Sendratasik Study Program - Habizar Habizar (Scope : Journal of English Language Teaching, 2022)
The present study aims to conduct an analysis of English course materials that is needed by students of Sendaratasik Study Program at Universitas Jambi. The participants of this study were seventy students of Sendratasik Study program who have taken the English course in the second semester. To collect the data, the researcher used questionnaires and interviews as the instruments. The results of the need analysis show that the English learning goals for the students of Sendratasik is to communicate using English actively. Most of them are interested in learning English because they want to improve their speaking skill in order to prepare themselves to fulfill their professional demand. Besides, there are also some of the students consider that the theoretical material such as grammar is also important to learn but the portion must be reduced. Learning grammar such as tenses, and so forth should be thought in the first two meetings only and then continued with practical activities such as writing, reading, listening, and speaking practice.